2011
DOI: 10.1080/09540121.2011.555744
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of poverty and inconsistent condom use among youth in urban Kenya

Abstract: To date, research on the link between poverty and unsafe sexual behaviors has utilized limited measures of socioeconomic status and has overlooked key dimensions of poverty at the individual level. This study explored how various dimensions of socioeconomic status are associated with inconsistent condom use and how these associations vary by gender. We analyzed unique life history survey data from 261 young men and women in Kisumu, Kenya, and conducted analyses based on 959 person-months in which respondents h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 31 publications
6
32
0
3
Order By: Relevance
“…The similar finding was validated by Cohen et al in his study, attributing cost as a barrier to condom use [40]. In addition, a study among youth in urban Kenya suggests that both household and individual level measures of socioeconomic status are important correlates of condom use and that individual economic resources plays a crucial role in negotiations over the highest level of usage [41]. Similarly, in other studies of female sex workers and truckers, it shows that the poor financial status is inversely associated with consistent condom use [42,43].…”
Section: Discussionsupporting
confidence: 57%
“…The similar finding was validated by Cohen et al in his study, attributing cost as a barrier to condom use [40]. In addition, a study among youth in urban Kenya suggests that both household and individual level measures of socioeconomic status are important correlates of condom use and that individual economic resources plays a crucial role in negotiations over the highest level of usage [41]. Similarly, in other studies of female sex workers and truckers, it shows that the poor financial status is inversely associated with consistent condom use [42,43].…”
Section: Discussionsupporting
confidence: 57%
“…Lower family income was associated with unprotected sex among men only. Other studies have also found an association between low socio-economic status and inconsistent condom use 20,21 . In a qualitative study with men without psychiatric disorders, one of the reasons for not using condoms was attributed to the high cost of this input 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study with men without psychiatric disorders, one of the reasons for not using condoms was attributed to the high cost of this input 22 . Moreover, these findings suggest that men with low income may have the least information about forms of HIV transmission and low decision-making power within their relationships to practice safe sex 20,21 . On the other hand, older age (> 40 years old) was associated with higher odds of unprotected sex among women only.…”
Section: Discussionmentioning
confidence: 99%
“…Dunkle et al (2007) working with a sample of 3,982 nonpregnant women in Soweto South Africa showed that those women who had experienced hunger, measured by a single question, in their households had 1.6 greater odds of reporting transactional sex with a nonprimary partner, and that transactional sex was associated with HIV infection in multivariate models. Davidoff-Gore et al (2011) also showed that among 261 Kenyan youth aged 18-24 years, food insufficiency, measured by a single question, was one of the few variables that was associated with inconsistent condom use, a risk factor for HIV and other STIs. This effect was strongest among food insufficient females who had five times greater odds of inconsistent condom use when compared with food sufficient females.…”
Section: Food Insecurity and Hiv/aidsmentioning
confidence: 99%